Konseling Kelompok Berbasis CBT : Strategi Intervensi Psikologis untuk Mengatasi Kecemasan, Prokrastinasi, dan Masalah Akademik - Mutia Najwa Khairunnisa; Wahdania Wahdania; Keisyah Nadya Zahro; Dwi Erma Nadhifa; Ratna Sari Dewi (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This article explores the effectiveness of the Cognitive Behavioral Therapy (CBT) approach in group counseling services to address various psychological issues experienced by students, such as anxiety, academic stress, low self-efficacy, and procrastination. Through a literature review of 20 articles published between 2015 and 2024, the study highlights that CBT-based group counseling has a positive impact on enhancing educational awareness, career maturity, self-confidence, self-control, and body image. Techniques such as cognitive restructuring, role playing, symbolic modeling, and active music therapy further reinforce the effectiveness of these interventions. However, the success of implementation greatly depends on the counselor’s skills, the intensity of sessions, and the participants’ active engagement. Therefore, CBT is considered a relevant and adaptable approach to be applied in group counseling within educational settings.